1995
DOI: 10.3109/10799899509079904
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a membrane-associated receptor for transforming growth factor type E

Abstract: We have identified the receptor for epithelial type transforming growth factor (TGFe). TGFe, a member of the epithelin/granulin family of proteins, is present primarily in tissues of epithelial origin. It is a powerful mitogen for epithelial and fibroblastic cells. TGFe, iodinated using an immobilized glucose oxidase-lactoperoxidase method, was chemically crosslinked to receptors on membranes isolated from SW-13 adrenal carcinoma cells by the crosslinker disuccinimidyl suberate (DSS). The receptor appears to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In situ hybridization has shown that the granulin/epithelin precursor mRNA is confined to epithelial cells in the kidney, intestine and lungs (Bhandari et al 1993). Because granulin/epithelin-related peptides act on epithelial cells, and epithelial cells express putative granulin/epithelin and TGFe receptors (Culouscou et al 1993, Parnell et al 1995, the expression of the precursor mRNA in epithelial cells in vivo supports the hypothesis of an autocrine role for members of the granulin/epithelin family in regulating epithelial cell growth. No hybridization was detected in muscle cells, connective tissue or endothelium (Bhandari Figure 3 The relative distribution of granulin mRNA in adult rat tissues.…”
Section: Tissue and Cell Distributionmentioning
confidence: 61%
See 2 more Smart Citations
“…In situ hybridization has shown that the granulin/epithelin precursor mRNA is confined to epithelial cells in the kidney, intestine and lungs (Bhandari et al 1993). Because granulin/epithelin-related peptides act on epithelial cells, and epithelial cells express putative granulin/epithelin and TGFe receptors (Culouscou et al 1993, Parnell et al 1995, the expression of the precursor mRNA in epithelial cells in vivo supports the hypothesis of an autocrine role for members of the granulin/epithelin family in regulating epithelial cell growth. No hybridization was detected in muscle cells, connective tissue or endothelium (Bhandari Figure 3 The relative distribution of granulin mRNA in adult rat tissues.…”
Section: Tissue and Cell Distributionmentioning
confidence: 61%
“…The 6-kDa peptide forms, the intact precursor, and related proteins such as TGFe, regulate the growth of epithelial and mesenchymal cells. Epithelial cells express putative receptors for granulin/epithelin peptides and TGFe (Culouscou et al 1993, Parnell et al 1995. Thus, although much remains to be clarified, granulin/epithelin polypeptides and related proteins are emerging as widely distributed potential autocrine and paracrine growth modulating factors for epithelial and mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time course studies of PCDGF synthesis and secretion in PC cells have shown that PCDGF is secreted as early as 2 hr after synthesis (data not shown). This observation and the fact that PC cells were growth-stimulated bv PCDGF (S) and presented PCDGF cell-surface binding sites (24) indicated that secreted PCDGF was an autocrine growth factor for the highly tumorigenic cells. Based on these results, it was hypothesized that PCDGF expression may be increased in tumorigenic cells when compared with their normal counterparts.…”
Section: Discussionmentioning
confidence: 95%
“…Up to now there is only one report about the characterization of receptor for epithelins (11). In addition, the binding sites on epithelial cells for TGF-e. a protein with the N-terminal sequence identical to the human granulin A, is reported (24). Scatchard analysis revealed there were two different binding sites with different affinity for epithelins and results from crosslinking showed there was a single band of ligand-receptor complex with about 145 kDa on the surface of MDA-MB-468.…”
Section: Discussionmentioning
confidence: 99%